2014
DOI: 10.36457/gizindo.v29i1.25
|View full text |Cite
|
Sign up to set email alerts
|

Studi Tentang Status Gizi Pada Rumahtangga Miskindan Tidak Miskin

Abstract: Nutritional status is a body health condition of a person or a group of people resulting from the consumption, absorption, and utilization of nutrients in food. This study aimed to asses nutritional status of children under five years, husbands, and wives in highland and coastal areas. This study used a case control group design. Case was poor household while control group was nonpoor household. The collected data from poor and nonpoor and from the highland and coastol areas were compared. Weight was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
3
0
10
Order By: Relevance
“…The Ministry of Health Republic of Indonesia (2013) indicated that boys were more at risk of being undernourished as stunting at 18 years of age was more common among boys than among girls (boys: 37.4%; girls: 26.2%). A small-scale study in Bogor and Indramayu districts also indicated that males were thinner than females in adulthood (Riyadi et al, 2006). This study found that 14.3% of adult males in poor households in Bogor had a BMI of less than 18.5, compared with 12.3% of adult females.…”
Section: The Indonesian Contextmentioning
confidence: 55%
“…The Ministry of Health Republic of Indonesia (2013) indicated that boys were more at risk of being undernourished as stunting at 18 years of age was more common among boys than among girls (boys: 37.4%; girls: 26.2%). A small-scale study in Bogor and Indramayu districts also indicated that males were thinner than females in adulthood (Riyadi et al, 2006). This study found that 14.3% of adult males in poor households in Bogor had a BMI of less than 18.5, compared with 12.3% of adult females.…”
Section: The Indonesian Contextmentioning
confidence: 55%
“…Apabila keluarga dengan pendapatan rendah mampu mengelola makanan yang bergizi dengan bahan yang sederhana dan murah maka pertumbuhan bayi juga akan menjadi baik 63 . Hal ini juga didukung oleh penelitian oleh Hadi yang menunjukkan tingkat pendapatan keluarga tidak berhubungan dengan status gizi TB/U dikarenakan indikator tersebut gambaran status gizi masa lampau sedangkan variabel pendapatan merupakan rekaman waktu terdekat 64 .…”
Section: Hubungan Karakteristik Ibu Dengan Kejadian Stuntingunclassified
“…Stunting juga dapat disebabkan oleh konsumsi pangan yang tidak sehat seperti minuman karbonasi yang mengganggu proses metabolisme dalam tulang. Faktor lain seperti sosial ekonomi yang berpengaruh terhadap kejadian stunting adalah pengeluaran pangan, pendidikan orang tua, pendapatan orang tua, dan status pekerjaan orang tua (Astri LD et al, 2006;Riyadi H et al, 2006;Arnelia et al, 2010).…”
Section: Pendahuluan Latar Belakangunclassified
“…Hasil yang berbeda ditunjukkan oleh penelitian Ramli et al (2009) yang menyatakan bahwa tingkat pendidikan formal ibu sangat berpengaruh terhadap kejadian stunting. Terkait dengan status ekonomi, yaitu pengeluaran pangan dan pendapatan orang tua, menurut Zottareli LK et al (2007), Riyadi H et al (2006), Aditiyanti (2010) dan Salimar (2009) menyatakan bahwa status ekonomi berhubungan dan berpengaruh signifikan terhadap stunting pada anak. Terkait dengan frekuensi konsumsi susu, terdapat perbedaan hasil antara penelitian ini dengan penelitian Hardinsyah et al (2008) yang menyatakan bahwa frekuensi konsumsi dan lama konsumsi susu berhubungan dengan tinggi badan remaja.…”
Section: Faktor Yang Berpengaruh Terhadap Kejadian Stunting Remajaunclassified